Nurses working in healthcare facilities during natural disasters: a qualitative enquiry. (6th August 2020) - Scrymgeour, G. C.; Smith, L.; Maxwell, H.; Paton, D.
Abstract : Aim: To explore the ability of nurses to be adequately ready for and to respond to a disaster caused by a natural hazard. Background: During a disaster involving a healthcare facility, nurses are commonly the largest group of healthcare workers impacted. The range of problems facing nurses working in healthcare facilities in Australia and New Zealand at the time of disasters triggered by earthquakes and bushfires have been underexamined. Methods: A qualitative enquiry was used to explore matters facing nurses working in residential healthcare facilities during a natural disaster. Inductive thematic analysis was used to identify the key themes from fifteen in‐depth interviews with nurses. Findings: Participants preserved a robust sense of professional duty, personal obligation and responsibility to their family, patients and the facility, demonstrating the ability to adapt, cope and respond despite experiencing diverse personal, structural and organizational barriers. Discussion: Support was provided for using interactive systems and socio‐ecological frameworks to better understand the contributions that individuals, teams and organizations make to facilitate the development and maintenance of adaptive capacity and resilience in a nursing workforce. An ecological model of adaptive capacity can be operationalized to guide education, training for nurses and the development of organizational systems and strategies. Conclusion: This study identified factors that help and hinder a nursing workforce's ability to prepared for, adapt to and learn from natural hazard disasters. Implications for Nursing Policy: This understanding of disaster preparedness and how this may be applied to enable the growth of adaptive nurses provides an insight for a global audience which also adds to nurse education, service delivery, organizational and policy development.